(untitled) (Research, Society and Development, 2021)
This study aimed to investigate music and its effects on anxiety control in elderly people who were in long-term care facilities. It is a research with a quantitative and qualitative approach. Eight elderly people cared for at a Long-Term Care Institution, located in the city of Caxias - Maranhão, were surveyed. For data collection, observation techniques, semi-directed interviews, sociodemographic characterization questionnaire, field diary and application of the Hamilton Anxiety Scale, an instrument used to measure the degree of anxiety of the interviewees, were used. In the results achieved, it was found that about 50% of the elderly presented, in the first assessment on an anxious state, a degree of anxiety classified as mild, moderate and severe and that after the application of the 05 musical repertoire sessions, they presented a decrease in these degrees, going to a minimum and moderate rating. A lower prevalence of degrees of anxiety was identified in elderly males. It was also found that upon contact with music, individuals recovered some memories, which is extremely important for the elderly population, as it keeps the cognitive functions active. In this way, the results show evidence that music can be used as a therapeutic tool to promote a balance in the anxious state of the elderly population.